In-situ growth carbon nanotube / lithium iron phosphate composite material and preparation method thereof

By growing carbon nanotubes in situ on the surface of lithium iron phosphate nanoparticles to form a conductive network, the problems of high cost and low performance improvement of carbon nanotubes and lithium iron phosphate composite materials in the prior art are solved, and high conductivity and excellent electrochemical performance are achieved.

CN119650606APending Publication Date: 2025-03-18JIANGSU CNANO TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311194479.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, when preparing carbon nanotubes and lithium iron phosphate composite materials, the cost is high and the performance improvement is not obvious, making it difficult to meet the conductivity requirements of the new generation of power batteries.

Method used

The carbon nanotube/lithium iron phosphate composite material grown in situ is used to inject an appropriate carbon source to grow carbon nanotubes in situ on the surface of lithium iron phosphate nanoparticles to form a conductive network and improve the conductivity of the material.

Benefits of technology

The conductivity of lithium iron phosphate positive electrode has been improved, which greatly improves the Coulomb efficiency and large-capacity charging and discharge performance during the first charge and discharge, and reduces the internal resistance of the battery and the charge and discharge polarization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650606A_ABST
    Figure CN119650606A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to an in-situ growth carbon nanotube / lithium iron phosphate composite material and a preparation method thereof. The in-situ growth carbon nano tube / lithium iron phosphate composite material comprises lithium iron phosphate nano particles and carbon nano tubes, under the action of a carbon source, the carbon nano tubes grow on the lithium iron phosphate nano particles in situ, and the carbon nano tubes form a conductive network on the surfaces of the lithium iron phosphate nano particles; the surfaces of the lithium iron phosphate nanoparticles are coated with carbon; the invention discloses an in-situ growth carbon nanotube / lithium iron phosphate composite material and a preparation method thereof, under the action of a carbon source, a carbon nanotube grows in situ on the positive electrode surface of lithium iron phosphate nanoparticles, and the carbon nanotube forms a conductive network in situ; by introducing the carbon source, smooth growth of the carbon nanotubes and formation of a conductive network among positive electrode particles are ensured, and the conductivity of the lithium iron phosphate positive electrode is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to an in-situ grown carbon nanotube / lithium iron phosphate composite material and a preparation method thereof. Background Art

[0002] Power batteries assembled with lithium iron phosphate cathodes have the advantages of low production cost, high safety, good cycle stability, and high energy density. Lithium iron phosphate cathode materials occupy the mainstream share of the power battery market. Due to the performance limitations of the material itself, the energy density of commercial lithium iron phosphate batteries at this stage is close to the theoretical upper limit. Therefore, lithium iron phosphate cathodes need to be improved to meet the requirements of the new generation of power batteries.

[0003] In related exploration and applications, carbon nanotubes have shown better physical properties. Compared with conventional commercially applied positive electrode carbon-coated materials, carbon nanotubes have better electron transmission capabilities. The ordered microscopic carbon tube structure can effectively improve the conductivity of positive electrode materials and improve the charge transmission performance within the material. Therefore, lithium iron phosphate positive electrodes modified with carbon nanotubes will have better electrochemical properties.

[0004] In-situ growth of carbon materials mainly composed of carbon nanotubes can reduce the contact area between the active material and the electrolyte, avoid side reactions between the positive electrode and the electrolyte, and improve its high temperature performance and cycle performance; in addition, the grown carbon nanotubes can also effectively inhibit the agglomeration and growth of the modified material particles, thereby maintaining the nanostructure of the particles and effectively reducing Li + The diffusion distance inside the active particles gives the material greater stability. At the same time, carbon nanotubes can build a fast conductive network with lithium iron phosphate, allowing electrons to quickly migrate between active materials during the charge and discharge process, reducing the battery's internal resistance and charge and discharge polarization.

[0005] In the prior art, when preparing carbon nanotube and lithium iron phosphate composite materials, lithium iron phosphate is grown on carbon nanotubes, or lithium iron phosphate is prepared into a slurry and then sprayed into a carbon source atmosphere, which is costly and has little significant performance improvement.

[0006] Therefore, it is urgent to develop a low-cost, low-conductivity carbon nanotube and lithium iron phosphate composite material. Summary of the invention

[0007] In order to meet the conductivity requirements of a new generation of lithium iron phosphate positive electrodes, the present application provides an in-situ grown carbon nanotube / lithium iron phosphate composite material and a preparation method thereof.

[0008] In a first aspect, the present application provides an in-situ grown carbon nanotube / lithium iron phosphate composite material, which adopts the following technical solution: An in-situ grown carbon nanotube / lithium iron phosphate composite material, the composite material comprises lithium iron phosphate nanoparticles and carbon nanotubes, wherein the carbon nanotubes are in-situ grown on the lithium iron phosphate nanoparticles under the action of a carbon source, the carbon nanotubes form a conductive network on the surface of the lithium iron phosphate nanoparticles; the surface of the lithium iron phosphate nanoparticles is coated with carbon.

[0009] Preferably, the carbon source is the first carbon source, and the first carbon source is at least one of methanol, ethanol, ethylene glycol, glycerol, methane, ethylene and propylene.

[0010] In the present application, by spraying a carbon source (i.e., the first carbon source) having a moderate boiling point, decomposition temperature, and bond energy, such a preferred carbon source can be evenly distributed on the surface of lithium iron phosphate nanoparticles during the spraying process, and carbon nanotubes are grown in situ on the surface of lithium iron phosphate nanoparticles to form a conductive network. Under the action of the first carbon source, the in-situ grown carbon nanotubes are more tightly combined with the lithium iron phosphate nanoparticles, so the positive electrode has a better conductivity.

[0011] In the present application, by injecting a carbon source and in-situ growing carbon nanotubes on the surface of lithium iron phosphate nanoparticles, a carbon nanotube conductive network that is more closely integrated with the positive electrode particles is established, thereby solving the conductivity problem of the lithium iron phosphate positive electrode and greatly improving the coulombic efficiency and large-capacity charge and discharge performance of the lithium iron phosphate positive electrode in the first charge and discharge.

[0012] Preferably, the lithium iron phosphate nanoparticles are of olivine structure, and the primary particle diameter thereof is 50nm-2000nm; more preferably 50nm-1000nm, and even more preferably 80nm-800nm; lithium iron phosphate nanoparticles of appropriate size facilitate electron transport and the formation of a carbon nanotube conductive network.

[0013] Preferably, the outer diameter of the in-situ grown carbon nanotubes is 5nm-100nm, preferably 8nm-70nm, and more preferably 15nm-50nm; the length of the in-situ grown carbon nanotubes is 300nm-20μm, preferably 500nm-20μm, and more preferably 2μm-20μm. Sufficiently long carbon nanotubes can effectively form a conductive network, and appropriate thickness can ensure the stability and continuity of the carbon nanotube network structure on the basis of small conductivity loss.

[0014] The in-situ grown carbon nanotube / lithium iron phosphate composite material synthesized by the method of the present application has a total carbon content of less than 3%, and the untreated powder of the carbon nanotube / lithium iron phosphate composite material has a powder resistivity of 2-10Ω·cm under a pressure of 10 MPa. This parameter is far superior to all lithium iron phosphate positive electrode materials on the market.

[0015] In a second aspect, the present application provides a method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material, using the following technical solution: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material, the preparation method comprising the following steps: preparing a slurry, drying the slurry, and sintering a precursor powder; wherein the step of sintering the precursor powder is as follows: sintering the precursor powder under an inert atmosphere, and introducing a carbon source to react while maintaining the inert atmosphere, thereby obtaining the carbon nanotube / lithium iron phosphate composite material.

[0016] Preferably, the carbon source is the first carbon source, and the first carbon source is at least one of methanol, ethanol, ethylene glycol, glycerol, methane, ethylene and propylene.

[0017] In the present application, during the sintering process of the precursor powder, the carbon source (the first carbon source) is sprayed or directly introduced to evenly cover the surface of the lithium iron phosphate nanoparticles with an organic carbon source. Under the action of high-temperature calcination, the organic molecules collide with each other or diffuse on the surface of the particles. Subsequently, the non-carbon elements in the organic molecules are volatilized, and the carbon atoms are connected together in a bending manner to form a cross-linked carbon nanotube network structure.

[0018] In the present application, a fixed furnace carbon source spraying / CVD method (ie, the first carbon source is sprayed during calcination) which is more suitable for large-scale production mode is adopted to ensure uniform carbon coating of the material and in-situ growth of carbon nanotubes.

[0019] Preferably, the amount of the first carbon source introduced is 5%-60% of the mass of the precursor powder.

[0020] Preferably, the introduction time of the first carbon source is 1 / 6-2 / 3 of the sintering time.

[0021] Preferably, the sintering temperature is 300-900° C., and the sintering time is 6-16 hours.

[0022] In the present application, by controlling the amount and time of the first carbon source introduced, the speed of spraying or direct introduction can be controlled, thereby controlling the diffusion and distribution of the organic carbon source and the final generation of the carbon nanotube conductive network, which not only effectively improves the efficiency of in-situ growth, but also allows the final synthesized composite material to have excellent conductivity.

[0023] Preferably, the inert atmosphere is at least one of nitrogen and argon.

[0024] Preferably, the steps of preparing the slurry are as follows: (1) mixing a lithium source, an iron source, a phosphorus source, and a second carbon source to obtain a mixed solution A; (2) preparing a third carbon source to obtain a mixed solution B; (3) Adding a vanadium source and a titanium source to the mixed solution A, mixing the mixture, adjusting the pH to acidic, and heating to react; then adding the mixed solution B to react to prepare a slurry.

[0025] Preferably, the molar ratio of the lithium source, the iron source, and the phosphorus source in step (1) is (0.9-1.5):1:(0.8-1.2); more preferably, the molar ratio of the lithium source, the iron source, and the phosphorus source in step (1) is (1.02-1.05):1:(0.95-1.05); The mass ratio of the second carbon source to the iron source in step (1) is (0.2-0.8):1.

[0026] The mass ratio of the second carbon source in step (1) to the third carbon source in step (2) is (0.5-2):1.

[0027] The molar ratio of the vanadium source in step (3) to the lithium source in step (1) is (0.0008-0.003):1, and the molar ratio of the titanium source in step (3) to the lithium source in step (1) is (0.0012-0.005):1; Preferably, the second carbon source is at least one of polyethylene glycol, polyvinyl pyrrolidone, water-soluble polyaniline, citric acid, sucrose, and cellulose; Preferably, the third carbon source is at least one of starch, sucrose, glucose, maltose, melamine and urea; and the solution is guided to react by adding the third carbon source.

[0028] Preferably, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate; Preferably, the iron source is at least one of ferric nitrate, ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous oxide, and iron powder; Preferably, the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, pyrophosphoric acid, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate.

[0029] Preferably, the vanadium source is at least one of vanadium pentoxide, vanadium dichloride, ammonium metavanadate, vanadium carbide, and vanadium zirconium blue; Preferably, the titanium source is at least one of titanium dioxide, ammonium titanyl oxalate, titanium tetrachloride, and titanyl sulfate.

[0030] Preferably, the heating method in step (3) is oil bath heating, the oil bath heating temperature is 60-120° C., and the oil bath heating time is 10-60 minutes; Preferably, the step of adjusting the pH is as follows: adding an alkaline solution to adjust the pH to 1-4; wherein the alkaline solution is at least one of lithium hydroxide solution, ammonia water, and hydrazine hydrate; Preferably, the time for adding the mixed solution B to react is 10-240 minutes.

[0031] Preferably, the step of drying the slurry is as follows: drying and crushing the prepared slurry to obtain a precursor powder; wherein the drying temperature is 80-180° C. and the drying time is 8-24 hours.

[0032] In a specific embodiment, a method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh the lithium source, iron source, phosphorus source and the second carbon source according to the molar ratio for later use; Wherein, the molar ratio of lithium source, iron source and phosphorus source is (0.9-1.5):1:(0.8-1.2); preferably, the molar ratio of lithium source, iron source and phosphorus source is (1.02-1.05):1:(0.95-1.05); The mass ratio of the second carbon source to the iron source is (0.2-0.8):1.

[0033] (2) The lithium source, iron source, phosphorus source and the second carbon source in the above raw materials are mixed to prepare a mixed solution A, wherein the mixed solution A is a mixed aqueous solution, a colloidal solution or a suspension.

[0034] The third carbon source is prepared as a mixed solution B, which is a mixed aqueous solution.

[0035] The mass ratio of the second carbon source to the third carbon source is (0.5-2):1.

[0036] (3) Mix the mixed solution of lithium source, iron source, phosphorus source and the second carbon source with a small amount of vanadium source and titanium source, and use alkaline solution to adjust the pH to between 1 and 4. Then put the solution system into an oil bath system. The oil bath temperature needs to be controlled at 60-120°C. Dry most of the solution in the oil bath state to form a yellow or brown solid with a fluffy structure.

[0037] Among them, the molar ratio of the vanadium source to the lithium source is (0.0008-0.003):1, and the molar ratio of the titanium source to the lithium source is (0.0012-0.005):1.

[0038] (4) After the above solution is kept at a constant temperature for 10 minutes to 60 minutes, the mixed solution B (i.e., the third carbon source) is added to the solution. After adding the third carbon source, the temperature is continued to be kept constant for 10 minutes to 240 minutes, and then the obtained product is dried at 80°C to 180°C for 8 hours to 24 hours.

[0039] (5) Subsequently, the product obtained above is collected and crushed, and then sintered at 300°C-900°C for 6-16 hours in an inert atmosphere. After the above sintering lasts for more than or equal to 1 / 3 and less than or equal to 5 / 6 of the total sintering time, the reducing carbon source (the first carbon source) is sprayed or directly introduced into the system under the inert atmosphere, and the sintering is continued until the first carbon source is introduced and the reaction is completed; after the reactor is cooled, the carbon nanotube / lithium iron phosphate composite material can be obtained. The above steps all require that the total carbon content of the composite material be controlled to be less than 3%.

[0040] The amount of the first carbon source introduced is 5%-60% of the mass of the precursor powder, and the time for introducing the first carbon source is 1 / 6-2 / 3 of the sintering time.

[0041] The sintering temperature is 300-900°C, and the sintering time is 6-16 hours.

[0042] Preferably, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate.

[0043] Preferably, the iron source is at least one of ferric nitrate, ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous oxide, and iron powder.

[0044] Preferably, the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, pyrophosphoric acid, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate.

[0045] Preferably, the first carbon source is at least one of methanol, ethanol, ethylene glycol, glycerol, methane, ethylene and propylene.

[0046] Preferably, the second carbon source is at least one of polyethylene glycol, polyvinyl pyrrolidone, water-soluble polyaniline, citric acid, sucrose and cellulose.

[0047] Preferably, the third carbon source is at least one of starch, sucrose, glucose, maltose, melamine and urea.

[0048] Preferably, the vanadium source is at least one of vanadium pentoxide, vanadium dichloride, ammonium metavanadate, vanadium carbide, and vanadium zirconium blue.

[0049] Preferably, the titanium source is at least one of titanium dioxide, ammonium titanyl oxalate, titanium tetrachloride, and titanyl sulfate.

[0050] Preferably, the alkaline solution is at least one of lithium hydroxide solution, ammonia water and hydrazine hydrate.

[0051] Preferably, the inert atmosphere is at least one of nitrogen and argon.

[0052] In the present application, a lithium iron phosphate precursor is synthesized by adopting an oil bath method, and by adding a third carbon source, the precursor is rapidly formed and has a nanoparticle structure at the microscopic level; subsequently, after a simple treatment, all impurities in the precursor are removed during the calcination stage.

[0053] Secondly, in this application, after a period of time in the calcination stage, the precursor powder is sprayed with a carbon source (the first carbon source), and the carbon nanotubes grow in situ on the positive electrode surface of the lithium iron phosphate nanoparticles, and the carbon nanotubes form a conductive network in situ. In this application, a specific carbon source, a special raw material ratio and doping elements are selected, and a spray method or chemical vapor deposition method is adopted to ensure the smooth growth of carbon nanotubes and the formation of a conductive network between positive electrode particles. This synthesis method is low-cost, rapid, and easy to industrialize in batches; and because the elements are evenly mixed in the precursor and the crystallization is good during the calcination stage, the positive electrode has excellent performance.

[0054] The in-situ growth of carbon nanotubes in the present application adopts a spray method or a chemical vapor deposition method (i.e., spray introduction or direct introduction). These two methods can effectively improve the degree of contact between lithium iron phosphate and the carbon source under a high-temperature calcination environment, and successfully improve the conversion efficiency of carbon nanotubes; and, due to the uniformly covered carbon layer and carbon nanotube network system, the conductivity of lithium iron phosphate is greatly improved.

[0055] The in-situ grown carbon nanotube / lithium iron phosphate composite material synthesized by the method of the present application has an extremely good powder resistivity while ensuring a low carbon content. At a pressure of 10 MPa, the powder resistivity is 2-10Ω·cm. While ensuring a discharge capacity of ≥155mAh / g, the powder resistivity of this material is much lower than similar products on the market (similar products are about 20-100Ω·cm). This performance is conducive to electron transmission, resulting in a high first efficiency of the battery assembled with this material, low internal resistance loss, and good high current charge and discharge effect.

[0056] The present application effectively solves the problem of low resistivity and poor conductivity of the lithium iron phosphate positive electrode, and increases the resistivity of the lithium iron phosphate positive electrode from the general 20-100Ω·cm to 2-10Ω·cm.

[0057] In summary, the present application includes at least one of the following beneficial technical effects: The present application discloses an in-situ grown carbon nanotube / lithium iron phosphate composite material and a preparation method thereof. Under the action of a carbon source, carbon nanotubes are in-situ grown on the positive electrode surface of lithium iron phosphate nanoparticles, and the carbon nanotubes form an in-situ conductive network. In the present application, by introducing a carbon source, the smooth growth of the carbon nanotubes and the formation of a conductive network between the positive electrode particles are ensured, thereby greatly improving the conductivity of the lithium iron phosphate positive electrode.

[0058] The synthesis method of the present invention is low-cost, rapid, and convenient for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a scanning electron microscope photograph of the in-situ grown carbon nanotube / lithium iron phosphate composite material prepared in Example 1.

[0060] Figure 2 This is a transmission electron microscope photograph of carbon nanotubes on the surface of the in-situ grown carbon nanotube / lithium iron phosphate composite material prepared in Example 2. DETAILED DESCRIPTION

[0061] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0062] The raw materials used in this application can be obtained commercially; The molecular weight of polyethylene glycol is 2000-6000; The molecular weight of water-soluble polyaniline is about 100,000; The molecular weight of polyvinyl pyrrolidone is 8000-10000; The molecular weight of cellulose is about 110,000 and it is soluble; Vanadium zirconium blue is Huayi Ceramics HC50114A; Iron powder was purchased from Shuanglong Mineral Products Processing Plant in Lingshou County; product specification: 1250 mesh.

[0063] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0064] Embodiment 1: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P of 1.02:1:0.97 for later use.

[0065] (2) Add 200 mL of water to 24.43 g of lithium hydroxide, 126.75 g of ferrous chloride, 111.58 g of ammonium dihydrogen phosphate and 40 g of polyethylene glycol, and mix to prepare a mixed aqueous solution.

[0066] 50 g of melamine was added to 100 mL of water to prepare a melamine solution.

[0067] (3) Mix a mixed aqueous solution of lithium hydroxide, ferrous chloride, ammonium dihydrogen phosphate and polyethylene glycol with 0.35 g of vanadium pentoxide and 0.5 g of titanium dioxide, and adjust the pH to between 2.2 and 2.4 with aqueous ammonia, then place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 75-85°C.

[0068] (4) After the solution was kept at a constant temperature for 20 minutes, melamine solution was added to the solution. After the melamine solution was added, the temperature was continued to be kept constant for 60 minutes, and then the obtained product was dried at 120° C. for 24 hours to obtain 352.76 g of precursor powder.

[0069] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 400°C for 2 hours and then at 720°C for 10 hours in a nitrogen atmosphere. After the product has been sintered at 720°C for 6 hours, 100 mL (111.3 g) of ethylene glycol was sprayed into the system for 4 hours while maintaining the nitrogen atmosphere. After waiting for the reactor to cool down, the carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0070] The carbon nanotube / lithium iron phosphate composite material prepared in this example was used to make a button battery, and the electrochemical performance of the material was tested. The specific method is as follows: (1) Preparation of positive electrode sheet of battery: The carbon nanotube / lithium iron phosphate composite material synthesized in this example and the binder polyvinylidene fluoride are weighed in a mass ratio of 95:3. The binder polyvinylidene fluoride and the organic solvent N-methylpyrrolidone are mixed and dissolved, and Super P (wherein Super P accounts for about 2% of the total mass of the carbon nanotube / lithium iron phosphate composite material and the binder) is added and stirred with the carbon nanotube / lithium iron phosphate composite material to form a slurry, which is coated on the surface of the carbon-coated aluminum foil, and rolled after drying to obtain the positive electrode sheet of the battery.

[0071] (2) Battery assembly and performance testing: Button cells were used to test the electrochemical properties of carbon nanotube / lithium iron phosphate composites.

[0072] The rolled positive electrode sheet was punched into a 13mm diameter positive electrode sheet, and the effective mass of the carbon nanotube / lithium iron phosphate composite material was calculated according to the composition of the positive electrode sheet after accurate weighing. The prepared positive electrode sheet, electrolyte, 18mm diameter PE separator, and 14mm diameter lithium sheet were used to assemble button batteries in a glove box.

[0073] (3) The specific capacity of the battery was tested using the Shenzhen Xinwei battery testing system. The test temperature was 25°C, and the charge and discharge rates were 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C for 10 cycles each, and the test was then returned to 0.1C for two cycles.

[0074] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this embodiment are as follows: at 0.1C, the discharge capacity reaches 162mAh / g, the coulombic efficiency in the first charge and discharge is as high as 99.48%, at 10C, the discharge capacity can still reach 111mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 159mAh / g. The powder resistivity of this sample is 2.1Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0075] The scanning electron microscope photo of the in-situ grown carbon nanotube / lithium iron phosphate composite material prepared in this example is as follows: Figure 1 As shown, from Figure 1 It can be seen that there are a large number of carbon nanotube structures in the carbon nanotube / lithium iron phosphate composite material.

[0076] Embodiment 2: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh lithium carbonate, ferric nitrate and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P of 1.03:1:1.03 for later use.

[0077] (2) Mix 38.06 g of lithium carbonate, 241.86 g of ferric nitrate, 118.48 g of ammonium dihydrogen phosphate and 60 g of citric acid, and add 240 mL of water to prepare a mixed aqueous solution.

[0078] Add 80 g of glucose to 200 mL of water to prepare a glucose solution.

[0079] (3) Mix a mixed aqueous solution of lithium carbonate, ferric nitrate, ammonium dihydrogen phosphate and citric acid with 0.72 g of ammonium metavanadate and 1.2 g of titanium dioxide, and adjust the pH to between 2.5 and 2.7 with aqueous ammonia, then place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 80-90°C.

[0080] (4) After the solution was kept at a constant temperature for 30 minutes, a glucose solution was added to the solution. After the glucose solution was added, the temperature was kept constant for 15 minutes, and then the obtained product was dried at 120° C. for 24 hours to obtain 538.40 g of precursor powder.

[0081] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 400°C for 2 hours and then at 760°C for 10 hours in a nitrogen atmosphere. After sintering at 760°C for 6 hours, 200 mL (158.2 g) of methanol was sprayed into the system for 4 hours while maintaining the nitrogen atmosphere. After waiting for the reactor to cool down, the carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0082] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 164mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 99.77%. At 10C, the discharge capacity can still reach 115mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 163mAh / g. The powder resistivity of this sample is 2.2Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0083] The transmission electron microscope photograph of the carbon nanotubes on the surface of the in-situ grown carbon nanotube / lithium iron phosphate composite material prepared in this example is as follows: Figure 2 As shown. Figure 2 It can be seen that the diameters of the carbon nanotubes are 25nm and 33nm, and they are multi-walled carbon nanotubes.

[0084] Embodiment 3: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh 70.34 g lithium nitrate, 151.91 g ferrous sulfate, and 118.75 g phosphoric acid (85% concentration) in a molar ratio of Li:Fe:P of 1.02:1:1.03 and set aside.

[0085] Weigh 75 g of water-soluble polyaniline and 80 g of starch for later use.

[0086] (2) The lithium nitrate, ferrous sulfate, phosphoric acid and water-soluble polyaniline in the above raw materials are mixed and then 400 mL of water is added to prepare a mixed aqueous solution.

[0087] 80 g of starch and 200 mL of water were mixed to prepare a starch solution.

[0088] (3) A mixed aqueous solution of lithium nitrate, ferrous sulfate, phosphoric acid and water-soluble polyaniline is mixed with 0.55 g of vanadium pentoxide and 0.84 g of ammonium titanium oxalate, and the pH is adjusted to between 2.0 and 2.2 using hydrazine hydrate, and then the solution system is placed in an oil bath system. The oil bath temperature needs to be controlled at 90-100°C.

[0089] (4) After the solution was kept at a constant temperature for 60 minutes, the starch solution was added to the solution. After the starch solution was added, the temperature was kept constant for 60 minutes, and then the obtained product was dried at 180° C. for 8 hours to obtain 496.00 g of precursor powder.

[0090] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 350°C for 2 hours and then at 740°C for 14 hours in an argon atmosphere. After sintering at 740°C for 8 hours, 50 mL (64.85 g) of propylene glycol was sprayed into the system for 8 hours while maintaining the argon atmosphere. After the reactor was cooled, a carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0091] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 158mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 99.21%. At 10C, the discharge capacity can still reach 106mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 159mAh / g. The powder resistivity of the sample is 2.9Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0092] Embodiment 4: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh 108.09 g of lithium dihydrogen phosphate and 79.844 g of ferric oxide in a molar ratio of Li:Fe:P of 1.04:1:1.04 for later use (the phosphorus source is also lithium dihydrogen phosphate).

[0093] Weigh 45 g of polyethylene glycol and 50 g of maltose for later use.

[0094] (2) After mixing the lithium dihydrogen phosphate, ferric oxide and polyethylene glycol in the above raw materials, add 150 mL of water and stir thoroughly to prepare a colloid.

[0095] 50 g of maltose was added to 100 mL of water to prepare a maltose solution.

[0096] (3) Mix the mixed colloid of lithium dihydrogen phosphate, ferric oxide and polyethylene glycol with 0.4 g of vanadium zirconium blue and 1.6 g of titanium tetrachloride, and adjust the pH to between 3.6 and 3.8 with ammonia water, then place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 100-120°C.

[0097] (4) After the solution was kept at a constant temperature for 60 minutes, maltose solution was added to the solution. After the maltose solution was added, the temperature was kept constant for another 60 minutes, and then the obtained product was dried at 180° C. for 16 hours to obtain 282.93 g of precursor powder.

[0098] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 350°C for 1 hour and then at 750°C for 15 hours in a nitrogen atmosphere. After sintering at 750°C for 12 hours, 100 mL (78.9 g) of ethanol was sprayed into the system for 3 hours while maintaining the nitrogen atmosphere. After waiting for the reactor to cool, the carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0099] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 155mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 98.77%. At 10C, the discharge capacity can still reach 102mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 156mAh / g. The powder resistivity of this sample is 4.9Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0100] Embodiment 5: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh 56.57 g of lithium dihydrogen phosphate, 55.845 g of iron powder, and 59.38 g of phosphoric acid (85% concentration) in a molar ratio of Li:Fe:P of 1.03:1:1.03 for later use (half of the phosphorus source is lithium dihydrogen phosphate).

[0101] Weigh 30 g of cellulose and 30 g of maltose for later use.

[0102] (2) Mix the lithium hydrogen phosphate, iron powder, phosphoric acid and cellulose in the above raw materials, add 150 mL of water and stir thoroughly to prepare a suspension.

[0103] Add 30 g of maltose to 100 mL of water to prepare a maltose solution.

[0104] (3) Mix the mixed suspension of lithium dihydrogen phosphate, iron powder, phosphoric acid and cellulose with 0.8 g of vanadium carbide and 2 g of titanyl sulfate, and adjust the pH to between 3.0 and 3.2 with ammonia water. Then, place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 110-120°C.

[0105] (4) After the solution was kept at a constant temperature for 60 minutes, maltose solution was added to the solution. After the maltose solution was added, the temperature was continued to be kept constant for 180 minutes, and then the obtained product was dried at 160° C. for 16 hours to obtain 231.80 g of precursor powder.

[0106] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 450°C for 1 hour and then at 800°C for 10 hours in a nitrogen atmosphere. After sintering at 800°C for 8 hours, 80L (52.4g) of methane was directly introduced into the system under a nitrogen atmosphere for 2 hours. After the reactor was cooled, a carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0107] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 157mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 99.01%. At 10C, the discharge capacity can still reach 108mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 156mAh / g. The powder resistivity of this sample is 7.1Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0108] Embodiment 6: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh 40.14 g of lithium phosphate, 241.86 g of ferric nitrate, and 79.94 g of phosphoric acid (85% concentration) in a molar ratio of Li:Fe:P of 1.04:1:1.04 for later use (1 / 3 of the phosphorus source is lithium phosphate).

[0109] Weigh 70 g of sucrose and 45 g of melamine for later use.

[0110] (2) Add 250 mL of water to the lithium phosphate, ferric nitrate, phosphoric acid and sucrose in the above raw materials, mix and stir thoroughly to prepare a suspension.

[0111] 45 g of melamine was added to 150 mL of water to prepare a melamine solution.

[0112] (3) Mix the mixed suspension of lithium phosphate, iron nitrate, phosphoric acid and sucrose with 0.65g of vanadium dichloride and 1.5g of ammonium titanyl oxalate, and adjust the pH to between 2.0 and 2.2 with ammonia water. Then, place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 90-110°C.

[0113] (4) After the solution was kept at a constant temperature for 60 minutes, melamine solution was added to the solution. After the melamine solution was added, the temperature was continued to be kept constant for 240 minutes, and then the obtained product was dried at 160° C. for 24 hours to obtain 476.94 g of precursor powder.

[0114] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 450°C for 1 hour and then at 800°C for 10 hours in a nitrogen atmosphere. After sintering at 800°C for 8 hours, 36.4L (23.85g) of methane was introduced into the system for 2 hours while maintaining the nitrogen atmosphere. After waiting for the reactor to cool down, the carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0115] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 159mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 98.91%. At 10C, the discharge capacity can still reach 101mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 158mAh / g. The powder resistivity of this sample is 4.2Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0116] Embodiment 7: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh 71.71 g lithium nitrate, 143.86 g ferrous oxalate, and 115.29 g phosphoric acid (85% concentration) in a molar ratio of Li:Fe:P of 1.03:1:1 and set aside.

[0117] Weigh 30 g of polyvinyl pyrrolidone and 60 g of glucose for later use.

[0118] (2) Mix the lithium nitrate, ferrous oxalate, phosphoric acid and polyvinyl pyrrolidone in the above raw materials, add 200 mL of water to prepare a mixed aqueous solution.

[0119] Mix 60 g of glucose with 150 mL of water to prepare a glucose solution.

[0120] (3) Mix a mixed aqueous solution of lithium nitrate, ferrous oxalate, phosphoric acid, and polyvinyl pyrrolidone with 1.15 g of vanadium pentoxide and 0.8 g of titanium dioxide, and adjust the pH to between 2.4 and 2.6 with aqueous ammonia. Then, place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 70-80°C.

[0121] (4) After the solution was kept at a constant temperature for 30 minutes, a glucose solution was added to the solution. After the glucose solution was added, the temperature was kept constant for another 30 minutes, and then the obtained product was dried at 120° C. for 24 hours to obtain 420.86 g of precursor powder.

[0122] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 400°C for 2 hours and then at 780°C for 10 hours in an argon atmosphere. After sintering at 780°C for 6 hours, 30L of propylene (51.53g) was introduced into the system under an argon atmosphere for 4 hours. After the reactor was cooled, a carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0123] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 160mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 99.32%. At 10C, the discharge capacity can still reach 109mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 159mAh / g. The powder resistivity of this sample is 3.4Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0124] Embodiment 8: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh 38.05 g of lithium carbonate, 241.86 g of ferric nitrate, and 118.75 g of phosphoric acid (85% concentration) in a molar ratio of Li:Fe:P of 1.03:1:1.03 and set aside.

[0125] Weigh 50 g of polyethylene glycol and 80 g of maltose for later use.

[0126] (2) Add 200 mL of water to the lithium carbonate, ferric nitrate, phosphoric acid and polyethylene glycol in the above raw materials to prepare a mixed aqueous solution.

[0127] 80 g of maltose was added to 200 mL of water to prepare a maltose solution.

[0128] (3) Mix the mixed aqueous solution of lithium carbonate, ferric nitrate, phosphoric acid and polyethylene glycol with 1.15g of vanadium zirconium blue and 2.0g of ammonium oxytitanium oxalate, and adjust the pH to between 2.8 and 3.0 with ammonia water. Then, place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 85-95°C.

[0129] (4) After the solution was kept at a constant temperature for 30 minutes, maltose solution was added to the solution. After the maltose solution was added, the temperature was kept constant for 30 minutes, and then the obtained product was dried at 120°C for 24 hours to obtain 528.66g of precursor powder.

[0130] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 400°C for 2 hours and then at 820°C for 6 hours in a nitrogen atmosphere. After sintering at 820°C for 4 hours, 35L (40.08g) of ethylene was introduced into the system for 2 hours while maintaining the nitrogen atmosphere. After the reactor was cooled, a carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0131] The carbon nanotube / lithium iron phosphate composite material prepared in this embodiment was tested by the electrochemical performance test method of Example 1, and the test results are as follows: at 0.1C, the discharge capacity reaches 159mAh / g, and the coulomb efficiency in the first charge and discharge is as high as 99.48%. At 10C, the discharge capacity can still reach 105mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 159mAh / g. The powder resistivity of this sample is 8.1Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0132] Embodiment 9: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P of 1.02:1:0.97 for later use.

[0133] (2) Add 200 mL of water to 24.43 g of lithium hydroxide, 126.75 g of ferrous chloride, 111.58 g of ammonium dihydrogen phosphate and 40 g of polyethylene glycol, and mix to prepare a mixed aqueous solution.

[0134] 50 g of melamine was added to 100 mL of water to prepare a melamine solution.

[0135] (3) Mix a mixed aqueous solution of lithium hydroxide, ferrous chloride, ammonium dihydrogen phosphate and polyethylene glycol with 0.35 g of vanadium pentoxide and 0.5 g of titanium dioxide, and adjust the pH to between 2.2 and 2.4 with aqueous ammonia, then place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 75-85°C.

[0136] (4) After the solution was kept at a constant temperature for 20 minutes, melamine solution was added to the solution. After the melamine solution was added, the temperature was continued to be kept constant for 60 minutes, and then the obtained product was dried at 120° C. for 24 hours to obtain 352.76 g of precursor powder.

[0137] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 400°C for 2 hours and then at 720°C for 10 hours in a nitrogen atmosphere. After the product has been sintered at 720°C for 2 hours, 190 mL (211.7 g) of ethylene glycol was sprayed into the system for 8 hours while maintaining the nitrogen atmosphere. After the reactor was cooled, the carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0138] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this embodiment are as follows: at 0.1C, the discharge capacity reaches 163mAh / g, the coulomb efficiency in the first charge and discharge is as high as 99.71%, at 10C, the discharge capacity can still reach 115mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 164mAh / g. The powder resistivity of this sample is 2.2Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0139] Embodiment 10: A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material comprises the following steps: (1) Weigh lithium hydroxide, ferrous chloride and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P of 1.02:1:0.97 for later use.

[0140] (2) Add 200 mL of water to 24.43 g of lithium hydroxide, 126.75 g of ferrous chloride, 111.58 g of ammonium dihydrogen phosphate and 40 g of polyethylene glycol, and mix to prepare a mixed aqueous solution.

[0141] 50 g of melamine was added to 100 mL of water to prepare a melamine solution.

[0142] (3) Mix a mixed aqueous solution of lithium hydroxide, ferrous chloride, ammonium dihydrogen phosphate and polyethylene glycol with 0.35 g of vanadium pentoxide and 0.5 g of titanium dioxide, and adjust the pH to between 2.2 and 2.4 with aqueous ammonia, then place the solution system in an oil bath system. The oil bath temperature needs to be controlled at 75-85°C.

[0143] (4) After the solution was kept at a constant temperature for 20 minutes, melamine solution was added to the solution. After the melamine solution was added, the temperature was continued to be kept constant for 60 minutes, and then the obtained product was dried at 120° C. for 24 hours to obtain 352.76 g of precursor powder.

[0144] (5) Subsequently, the product obtained above was collected and crushed, and then sintered at 400°C for 2 hours and then at 720°C for 10 hours in a nitrogen atmosphere. When the product has been sintered at 720°C for 8 hours, 190 mL (211.7 g) of ethylene glycol was sprayed into the system for 2 hours while maintaining the nitrogen atmosphere. After the reactor was cooled, the carbon nanotube / lithium iron phosphate composite material was obtained, and the total carbon content of the final product carbon nanotube / lithium iron phosphate composite material was less than 3%.

[0145] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this embodiment are as follows: at 0.1C, the discharge capacity reaches 159mAh / g, the coulomb efficiency in the first charge and discharge is as high as 99.71%, at 10C, the discharge capacity can still reach 107mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C can still reach 158mAh / g. The powder resistivity of this sample is 2.9Ω·cm under a pressure of 10 MPa. This shows that the carbon nanotube / lithium iron phosphate composite material synthesized in this embodiment has good electrochemical properties and can be widely used in power batteries and energy storage fields.

[0146] Comparative Example 1: The difference between this comparative example and Example 1 is that ethylene glycol is not sprayed in the sintering stage in step (5). At this time, the positive electrode material does not contain carbon nanotubes.

[0147] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 112mAh / g, the coulomb efficiency in the first charge and discharge is 85.21%, at 10C, the discharge capacity is 55mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 103mAh / g. The powder resistivity of the sample is 65.9Ω·cm under a pressure of 10 MPa. The performance is degraded.

[0148] Comparative Example 2: The difference between this comparative example and Example 1 is that no vanadium source (vanadium pentoxide) and titanium source (titanium dioxide) are added in step (3). At this time, the primary particles of the positive electrode material become larger, and the uniformity of the solid after the solution reaction decreases.

[0149] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 135mAh / g, the coulomb efficiency in the first charge and discharge is 92.40%, at 10C, the discharge capacity is 81mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 130mAh / g. The powder resistivity of the sample is 40.3Ω·cm under a pressure of 10 MPa. The performance is deteriorated.

[0150] Comparative Example 3: The difference between this comparative example and Example 1 is that polyethylene glycol is not added in step (2). At this time, the evaporation speed of the precursor solution is significantly slowed down, and the positive electrode material shows obvious sintering phenomenon.

[0151] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 60mAh / g, the coulomb efficiency in the first charge and discharge is 62.75%, at 10C, the discharge capacity is 20mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 48mAh / g. The powder resistivity of this sample is 182.3Ω·cm under a pressure of 10 MPa. The performance has been greatly deteriorated.

[0152] Comparative Example 4: The difference between this comparative example and Example 1 is that the time for spraying ethylene glycol during the sintering stage in step (5) is controlled to be 1 hour. At this time, the carbon nanotube content in the positive electrode material is relatively low.

[0153] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 139mAh / g, the coulomb efficiency in the first charge and discharge is 92.51%, at 10C, the discharge capacity is 75mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 136mAh / g. The powder resistivity of the sample is 31.9Ω·cm under a pressure of 10 MPa. The performance is degraded.

[0154] Comparative Example 5: The difference between this comparative example and Example 1 is that in step (5), the time for spraying ethylene glycol during the sintering stage is controlled to be 9 hours. At this time, the carbon nanotubes in the positive electrode material are adhered and the diameter exceeds 80 nm.

[0155] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 130mAh / g, the coulomb efficiency in the first charge and discharge is 99.11%, at 10C, the discharge capacity is 91mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 131mAh / g. The powder resistivity of this sample is 3.1Ω·cm under a pressure of 10 MPa. The powder resistivity has not deteriorated, but the battery capacity cannot reach the commercial standard.

[0156] Comparative Example 6: The difference between this comparative example and Example 1 is that in step (5), the mass of ethylene glycol sprayed into the sintering stage is controlled to be 2% of the mass of the precursor, that is, 7.06 g. At this time, the carbon tube content in the positive electrode material is relatively low.

[0157] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 123mAh / g, the coulomb efficiency in the first charge and discharge is 88.98%, at 10C, the discharge capacity is 81mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 122mAh / g. The powder resistivity of the sample is 41.1Ω·cm under a pressure of 10 MPa. The performance is degraded.

[0158] Comparative Example 7: The difference between this comparative example and Example 1 is that in step (5), the mass of ethylene glycol sprayed into the sintering stage is controlled to be 4% of the mass of the precursor, that is, 14.11 g. At this time, the carbon tube content in the positive electrode material is relatively low.

[0159] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 139mAh / g, the coulomb efficiency in the first charge and discharge is 91.22%, at 10C, the discharge capacity is 90mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 137mAh / g. The powder resistivity of this sample is 25.2Ω·cm under a pressure of 10 MPa. The performance is degraded, but its performance is better than that of comparative example 6.

[0160] Comparative Example 8: The difference between this comparative example and Example 1 is that in step (5), the mass of ethylene glycol sprayed into the sintering stage is controlled to be 65% of the mass of the precursor, that is, 229.29 g. At this time, the carbon tubes in the positive electrode material are relatively thick (>60 nm).

[0161] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 141mAh / g, the coulomb efficiency in the first charge and discharge is 98.44%, at 10C, the discharge capacity is 98mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 140mAh / g. The powder resistivity of this sample is 2.5Ω·cm under a pressure of 10 MPa. The powder resistivity meets the requirements of this application, but the battery capacity is degraded and cannot meet the commercial use scenario.

[0162] Comparative Example 9: The difference between this comparative example and Example 1 is that in step (5), the mass of ethylene glycol sprayed into the sintering stage is controlled to be 80% of the mass of the precursor, that is, 282.21 g. At this time, the carbon tubes in the positive electrode material are relatively thick (>80 nm).

[0163] The electrochemical performance test results of the carbon nanotube / lithium iron phosphate composite material prepared in this comparative example are as follows: at 0.1C, the discharge capacity is 125mAh / g, the coulomb efficiency in the first charge and discharge is 98.71%, at 10C, the discharge capacity is 88mAh / g, and after completing the high-rate charge and discharge cycle, the discharge capacity at 0.1C is 127mAh / g. The powder resistivity of this sample is 2.7Ω·cm at a pressure of 10 MPa. The powder resistivity meets the requirements of this application, but the battery capacity is degraded and cannot meet the commercial use scenario, and the performance of this comparative example is inferior to that of comparative example 8.

[0164] The in-situ grown carbon nanotube / lithium iron phosphate composite material provided by the present application has a specific carbon nanotube conductive network structure, which makes the material have the characteristics of high conductivity and high energy density, and has good properties under high current charging and discharging, and can meet the needs of power batteries for fast charging. The process steps provided by the present application will not produce wastewater pollution, have low requirements for sintering, and do not require sanding or other complex treatments, which has positive significance in terms of environmental protection, energy conservation, and cost control.

[0165] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. An in-situ grown carbon nanotube / lithium iron phosphate composite material, characterized in that: The composite material includes lithium iron phosphate nanoparticles and carbon nanotubes, wherein the carbon nanotubes are in-situ grown on the lithium iron phosphate nanoparticles under the action of a carbon source, and the carbon nanotubes form a conductive network on the surface of the lithium iron phosphate nanoparticles; and the surface of the lithium iron phosphate nanoparticles is coated with carbon.

2. The in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 1, characterized in that: The carbon source is a first carbon source, and the first carbon source is at least one of methanol, ethanol, ethylene glycol, glycerol, methane, ethylene, and propylene.

3. The in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 1, characterized in that: The primary particle diameter of the lithium iron phosphate nanoparticles is 50nm-2000nm; the outer diameter of the in-situ grown carbon nanotubes is 5nm-100nm; and the length is 300nm-20μm.

4. A method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material, characterized in that: The steps of the preparation method are as follows: preparation of slurry, drying of the slurry and sintering of precursor powder; wherein, the step of sintering the precursor powder is as follows: sintering the precursor powder under an inert atmosphere, maintaining the inert atmosphere, introducing a carbon source for reaction, and obtaining a carbon nanotube / lithium iron phosphate composite material.

5. The method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 4, characterized in that: The carbon source is the first carbon source, which is at least one of methanol, ethanol, ethylene glycol, propylene glycol, methane, ethylene, and propylene; the amount of the first carbon source introduced is 5%-60% of the mass of the precursor powder, and the introduction time of the first carbon source is 1 / 6-2 / 3 of the sintering time.

6. The method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 4, characterized in that: The sintering temperature is 300-900° C., and the sintering time is 6-16 hours; the inert atmosphere is at least one of nitrogen and argon.

7. The method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 4, characterized in that: The steps for slurry preparation are as follows: (1) mixing a lithium source, an iron source, a phosphorus source, and a second carbon source to obtain a mixed solution A; (2) preparing a third carbon source to obtain a mixed solution B; (3) adding a vanadium source and a titanium source to the mixed solution A, adjusting the pH to acidic, and heating to react; Then, the mixed solution B was added to react to obtain a slurry.

8. The method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 7, characterized in that: In step (1), the molar ratio of the lithium source, the iron source, and the phosphorus source is (0.9-1.5):1:(0.8-1.2); the mass ratio of the second carbon source to the iron source is (0.2-0.8):1; The mass ratio of the second carbon source in step (1) to the third carbon source in step (2) is (0.5-2):1; The molar ratio of the vanadium source in step (3) to the lithium source in step (1) is (0.0008-0.003):1, and the molar ratio of the titanium source in step (3) to the lithium source in step (1) is (0.0012-0.005):1; The second carbon source is at least one of polyethylene glycol, polyvinyl pyrrolidone, water-soluble polyaniline, citric acid, sucrose and cellulose; The third carbon source is at least one of starch, sucrose, glucose, maltose, melamine and urea; The lithium source is at least one of lithium hydroxide, lithium carbonate, lithium nitrate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate; The iron source is at least one of ferric nitrate, ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous oxide, and iron powder; The phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, pyrophosphoric acid, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and lithium phosphate; The vanadium source is at least one of vanadium pentoxide, vanadium dichloride, ammonium metavanadate, vanadium carbide, and vanadium zirconium blue; The titanium source is at least one of titanium dioxide, ammonium titanyl oxalate, titanium tetrachloride and titanyl sulfate.

9. The method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 7, characterized in that: The heating temperature in step (3) is 60-120° C. and the heating time is 10-60 minutes; The step of adjusting pH is as follows: adding an alkaline solution to adjust the pH to 1-4; wherein the alkaline solution is at least one of lithium hydroxide solution, ammonia water, and hydrazine hydrate; The time for adding the mixed solution B to react is 10-240 minutes.

10. The method for preparing an in-situ grown carbon nanotube / lithium iron phosphate composite material according to claim 4, characterized in that: The steps of drying the slurry are as follows: drying and crushing the prepared slurry to obtain precursor powder; wherein the drying temperature is 80-180° C. and the drying time is 8-24 hours.

Citation Information

Cited By

  • Conductive carbon fiber lithium iron manganese phosphate composite material and preparation method thereof

    CN120575363A